2002
DOI: 10.3354/meps235217
|View full text |Cite
|
Sign up to set email alerts
|

Parasite distribution on client reef fish determines cleaner fish foraging patterns

Abstract: Recent evidence suggests that cleaner fish Labroides dimidiatus effectively control parasite densities on client reef fish that actively visit them to have parasites and dead or infected tissue removed. These findings support the hypothesis that clients benefit from cleaning. However, they do not show how cleaners reduce the parasite load of their clients. Cleaners could selectively feed on parasites or parasite removal could be a side product of cleaners foraging indifferently on the client surface, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Inspection duration has been suggested to be a function of body size and ectoparasite load, as larger clients harbor more parasites leading to greater foraging success for cleaners (Grutter 1995;Bshary and Grutter 2002;Becker and Grutter 2005), but cleaner group size may prolong cleaning interactions as well (Gingins and Bshary 2015). Consequently, cleaners may prefer larger bodied clients.…”
Section: Client Diversity Frequency and Durationmentioning
confidence: 96%
“…Inspection duration has been suggested to be a function of body size and ectoparasite load, as larger clients harbor more parasites leading to greater foraging success for cleaners (Grutter 1995;Bshary and Grutter 2002;Becker and Grutter 2005), but cleaner group size may prolong cleaning interactions as well (Gingins and Bshary 2015). Consequently, cleaners may prefer larger bodied clients.…”
Section: Client Diversity Frequency and Durationmentioning
confidence: 96%
“…Client traits that may affect a cleaner's choice of clients include client's ectoparasite load (Gorlick 1984;Bshary and Grutter 2002b), size (Grutter et al 2005), relative density (Adam 2010), and solicitation behaviour (Losey 1974). Early studies noted that Labroides spp.…”
Section: Introductionmentioning
confidence: 99%
“…When investigating how cleaners forage, Bshary and Grutter [25] showed that L. dimidiatus spent more time on, and took more feeding bites from the parasitized side of the surgeonfish Ctenochaetus striatus compared to the unparasitized side. They concluded that cleaners optimize their foraging by concentrating on areas of a client's body where parasites are located.…”
Section: Introductionmentioning
confidence: 99%